Nursing care for pregnant women attended in Primary health Care network: integrative review (Research, Society and Development, 2022)
The objective is to analyze the Nursing care provided to pregnant women in the Primary Health Care network during prenatal care. This is an integrative review, where bibliographical research with a qualitative and quantitative approach was carried out. A total of 118 articles published between 2017 and 2022 were selected, where only 10 articles were analyzed and identified, which deal with the Nursing care provided to pregnant women who are assisted in the Primary Health Care network. Therefore, it is noted that the present research is of great importance for Nursing, also emphasizing the promotion of improvements in prenatal care provided, through the qualification of professionals and safe, humane and quality monitoring.